STUDI EMPIRIS TENTANG PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) PERIODE 2008 â 2010 - MasÃ¢Â€Â™an Effendi, 10.52.02.0129 (Students Journal of Accounting and Banking, 2013)
The objectives of this study are to analyze an empirical study of the impact of intellectual capital on business performance. For accounting ratios: Â Return on Assets (ROA), Market to Book Value (MBV), Assets Turnover (ATO),Â and Return On Equity (ROE). Data were used from constituent companies of Indonesia Capital Market Directory (ICMD) Â 2008-2010. The model that used to measure intellectual capital was Pulic model agregatly using Value Added Intellectual Coefficient (VAIC) include the component of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE). The result show: agregatly, intellectual capital (VAIC) has a significant impact onÂ Market to Book Value (MBV), Assets Turnover (ATO), and Return on Equity (ROE). But has no significant for Return onÂ Assets (ROA), Keywords: Intellectual Capital, Financial Performance, Business Manufacture,ICMD